Coaching on the talent pathway: Understanding the influence of developmental experiences on coaching philosophy - Williams, G. G.; MacNamara, A. (International Sport Coaching Journal, 2021)
There is compelling evidence supporting the critical role of high-quality coaching practice in supporting talented youth athletes through and beyond the talent pathway. The purpose of this study was to explore the coaching philosophies of ex-talent pathway athletes and how the meaning and purpose of their coaching in a talent pathway was influenced by their previous pathway experience. Nine participants were purposefully sampled based on their prior involvement as a youth athlete in a talent pathway and current involvement coaching in a talent pathway. The participants identified how their pathway experience influenced their coaching philosophy and applied coaching practice. Specifically, the participants described how their own youth sport experience influenced their current coaching practice through the formation of a developmental coaching philosophy, through their applied coaching practice orientated towards supporting individual development, and by using their previous pathway experience to support coaching success. These findings suggest that the philosophy underpinning talent pathway coaches` practice was influenced by their own pathway experience, and the purpose of their practice was orientated to positively impact youth development for and beyond sport. Thus, talent pathways in sport have the capability to be recognised as positively influencing the developmental experiences of future coaching practitioners.